2021
DOI: 10.1021/acs.chemmater.1c02868
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Compartmentalization Strategy for Coating Polymers with Self-Organized Prismatic Films

Abstract: Biomineralization provides load-bearing and protective functions to living organisms by reinforcing soft tissues. Translation of biomineralization principles to materials science in a controlled and self-organized fashion is highly desirable but challenging. A major lesson from natural systems is that crystallization may be controlled by compartmentalization and templating. Here, we develop a crystallization technique based on graphene oxide-mediated compartmentalization and on templating prismatic growth of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Microscratch experiments were performed to further evaluate the adhesion of the modified epoxy resin to copper (Figure e,f). , As shown in Figure g, the critical loads of BCB-DA-0 and BCB-DA-10 were 4.78 and 5.77 N, respectively. These results showed that introducing the BCB-DA structure can improve the adhesion between epoxy resins and copper.…”
Section: Resultsmentioning
confidence: 99%
“…Microscratch experiments were performed to further evaluate the adhesion of the modified epoxy resin to copper (Figure e,f). , As shown in Figure g, the critical loads of BCB-DA-0 and BCB-DA-10 were 4.78 and 5.77 N, respectively. These results showed that introducing the BCB-DA structure can improve the adhesion between epoxy resins and copper.…”
Section: Resultsmentioning
confidence: 99%
“…Reproduced with permission. [ 123a ] Copyright 2020, Wiley‐VCH. j) Demonstration of using the ceramic fibrous membrane as a wire to light a bulb.…”
Section: Applicationsmentioning
confidence: 99%
“…Reproduced with permission. [ 123a ] Copyright 2020, Wiley‐VCH. k) Ammonia yields and Faradaic efficiencies of c‐TiO 2 sponges at different potentials for 2 h. Reproduced with permission.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As this process involves the transition from nanoscale to macroscale, it is also referred to as a bottom‐up process 14,36 . As proven in many experiments, biomineralization is one such bottom‐up mineralization process 14,34,37 . The PILP process requires a class of polymers that stabilizes the amorphous precursors to achieve liquid–liquid phase separation.…”
Section: Introductionmentioning
confidence: 99%